2005
DOI: 10.1026/0049-8637.37.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Lernstrategien und Lernerfolg im Studium:

Abstract: Zusammenfassung. Das von Wild und Schiefele (1994) vorgestellte Inventar zur Erfassung von Lernstrategien im Studium (LIST) wird an einer Stichprobe von N = 577 berufstätigen Studierenden vier unterschiedlicher Hochschulen untersucht. Die von Wild und Schiefele angenommene Struktur der kognitiven, ressourcenbezogenen und metakognitiven Lernstrategien wird hier erstmals faktorenanalytisch überprüft. Darüber hinaus wird erstmals die dreifaktorielle Struktur der metakognitiven Lernstrategien mit dem LIST-Inventar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 13 publications
(14 reference statements)
1
20
0
6
Order By: Relevance
“…Both instruments differentiate between two classification levels: Higher-level cognitive, metacognitive, and resource-related strategies and lower-level structures assessed by the more specific subscales of the questionnaire (Wild & Schiefele, 1994). The methodological basis of the LIST, however, has been criticized because recent work did not confirm the proposed higher-order three-factor structure (Boerner, Seeber, Keller, & Beinborn, 2005). Instead, it was suggested that a two-factor model including the second-order factors ''learning discipline'' and ''elaboration'' may be more appropriate to account for the learning strategies assessed by the LIST (Blickle, 1996).…”
Section: Learning Strategies and Personalitymentioning
confidence: 97%
See 1 more Smart Citation
“…Both instruments differentiate between two classification levels: Higher-level cognitive, metacognitive, and resource-related strategies and lower-level structures assessed by the more specific subscales of the questionnaire (Wild & Schiefele, 1994). The methodological basis of the LIST, however, has been criticized because recent work did not confirm the proposed higher-order three-factor structure (Boerner, Seeber, Keller, & Beinborn, 2005). Instead, it was suggested that a two-factor model including the second-order factors ''learning discipline'' and ''elaboration'' may be more appropriate to account for the learning strategies assessed by the LIST (Blickle, 1996).…”
Section: Learning Strategies and Personalitymentioning
confidence: 97%
“…Learning discipline contains the scales Organization, Rehearsal, Meta-cognition, Effort, Attention, Time management and Learning environment, whereas the scales Relationships, Critical evaluation, Learning with fellow students and Literature build the factor elaboration. For details on reliability and validity see Boerner et al (2005).…”
Section: Listmentioning
confidence: 99%
“…German Learning Strategy Inventory (LIST). The inventory (Wild & Schiefele, 1994) distinguishes three groups of strategies -cognitive, metacognitive, and resource management strategies, which are comprised of several subscales: organization (α = .83), elaboration (α = .81), repetition (α = .63), planning (α = .77), monitoring (α = .66), regulation (α = .78), effort (α = .70), time management (α = .86), and joint learning (α = .87). All items were measured on 5-point scales (1 = very seldom, 5 = very often).…”
Section: Methodsmentioning
confidence: 99%
“…We then inquired about learning strategies via our constructed self-testing scale (ST-scale, see below), followed by other items (e.g., generation, spaced/interleaved learning), which we included for distraction (and for reasons not relevant to the present study: replication of a previous published relationship of NFC and goals orientations with learning activities by the first author). Thereafter, items of the German Learning Strategy Inventory LIST (Schiefele & Wild, 1994) followed, which served to validate our newly constructed scale. We embedded the measurement of students' test anxiety (PAF; Hodapp, Rohrmann & Ringeisen, 2011) within other questionnaires (e.g.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Experimental studies often report that adequate correlations are not found or are showing relative low coherence (Artelt, 1999;Schiefele, 2005 2 (Schiefele, 2005). We assume like others that the reasons for the low coherence could be allocated on the one hand in the validity and/or reliability of measuring learning performance but also on the other hand to in the research setting not considering variables which affect the relationship between learning strategies and learning performance (Boerner, Seeber, Keller & Beinborn, 2005). For instance Artelt (1999) and Schiefle (2005) point out that the use of research designs which are close to the observation of behaviour lead to higher coherence.…”
mentioning
confidence: 99%